An Operations management analysis on Air Hauling Services, Ltd. - Balaguer, Aimee O.; Flores, Ma. Criselda; Gonzales, Cheryl Victoria (Diliman, Quezon City College of Engineering, 2004)
One of the most common outsourced services is the transportation of goods between buyers and sellers. Benefits of outsourcing this activity include lower cost, elimination of maintenance costs, reduced manpower, as well as reduction in planning and scheduling. AR Hauling Services Ltd. is a company that provides this service. It has two 2-tonner and three 4-tonner refrigerated trucks, and its primary customer is San Miguel Corporation. The company's capacity is constrained by the number-coding scheme, thus only 11 trips can be made per week by each truck instead of 12 trips. For the 2-tonners, the effective capacity is 2288 trips, and for the 4-tonner, 3432 trips. With actual demand of 907 trips and 972 for the 2-tonner and 4-tonner trucks respectively, percent utilization is only 39.64% for the 2-tonner 28.32% for the 4-tonner. These lead to an opportunity cost of P10,142,246.40 in truck trips. These values were computed for 2 years. Examination of the current system showed that under-utilization of trucks and not being able to accommodate new clients were the problems that hinder the company from realizing its opportunity cost. These could be addressed by properly scheduling trucks. Costs could also be reduced further by establishing a suitable staffing plan. Historical data shows that demand is fairly stable for the whole year, except for a slight increase in November and December. On a daily level, average demand for both truck types is less than 1 on Mondays, but around 1.5 trips per truck type for the rest of the week. For November and December, there is a marked increase in demand during Tuesdays (2.61 trips ) and Saturdays (2.19 trips.) Using this data, simulation of the system on a daily basis was performed to determine the utilization of trucks. The measures considered by the group as useful for analyzing the system are the number of failed arrivals in the system, the total exits, and the percent of the time the trucks are empty. These were used, first, to determine which trucks can be made available to other clients, two, as a measure of variability of the demand for that type of truck and three, to find out how many trips are left after the primary customer's demands have been met. Incorporating company policies into the simulation output determined how many trips by each truck type can be offered to new clients for each day, while taking into account the different demand levels of November and December. After which, an Excel-based program that incorporated the truck trips that can be offered to potential customers for a whole year at different time periods was recommended. The current workforce level consists of fifteen workers, with three workers for each truck. Data demonstrates that the company could meet at least 90% of its primary customer's demand at all times using only nine workers. Thus it was recommended that the company reduce its workforce to this level. Capacity gaps, especially in November and December, could be filled using part-time workers. This recommendation is valid since workers are readily available. No additional costs will be incurred by this decision since there is no laying off and hiring costs, and the company's policy is no-work, no-pay. Expected savings from this move is attributed to the company's SSS contribution, which is P9576.00 for a year. Thus arrangements should be made with a potential customer while following the schedule of available extra truck trips on designated periods so as to avoid conflict with previous commitment to San Miguel. Utilizing these free trips would result to P2,427,219.00 per year. If the demand of San Miguel or the new client becomes progressively higher that the number of free trips, the company may now consider hiring the part-time workers as regular employees. AR Hauling may also consider buying new trucks depending on the demand of the clients. This decision requires a substantial amount of investment; therefore, before buying new trucks, the management must be really sure of the expected demand of the customers.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: AR Hauling Services; Production engineering